2021
DOI: 10.1111/obr.13168
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral weight management interventions in metabolic and bariatric surgery: A systematic review and meta‐analysis investigating optimal delivery timing

Abstract: Summary Metabolic and bariatric surgery (MBS) yields unprecedented clinical outcomes, though variability is high in weight change and health benefits. Behavioral weight management (BWM) interventions may optimize MBS outcomes. However, there is a lack of an evidence base to inform their use in practice, particularly regarding optimal delivery timing. This paper evaluated the efficacy of BWM conducted pre‐ versus post‐ versus pre‐ and post‐MBS. The review followed the Preferred Reporting Items for Systematic Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 107 publications
(482 reference statements)
1
21
0
Order By: Relevance
“…Recently, a meta-analysis was published on the optimal delivery time of behavioural weight-management interventions. 29 Although results were in line with ours, stating that an APP had no statistical significant effect on WL, they found that included studies had high risk of bias and that studies on nonweight-related outcomes are needed, on which we contributed by analysing protein intake and the number of no-shows.…”
Section: Discussionsupporting
confidence: 83%
“…Recently, a meta-analysis was published on the optimal delivery time of behavioural weight-management interventions. 29 Although results were in line with ours, stating that an APP had no statistical significant effect on WL, they found that included studies had high risk of bias and that studies on nonweight-related outcomes are needed, on which we contributed by analysing protein intake and the number of no-shows.…”
Section: Discussionsupporting
confidence: 83%
“…Recent research suggests that the most optimal timing for intervention is postoperative (Cassin et al, 2020;David et al, 2020;Julien et al, 2021;Nijamkin et al, 2012Nijamkin et al, , 2013. For instance, Nijamkin et al Whether postoperative intervention should be indicated only for patients experiencing weight and mental problems, or should be indicated for all patients, is another issue that needs to be researched.…”
Section: Discussionmentioning
confidence: 99%
“…This step is critical to integrating previously accumulated knowledge on adjunct behavioral interventions in patients undergoing BS. The first part of this step focused on the timing of the interventions relative to surgery (Julien et al, 2021). Other sections of the living systematic review include evaluating the quality of trials using the NPI-CONSORT statement (Boutron et al, 2017) and the TIDieR checklist (Hoffmann et al, 2014) and deconstructing the interventions into their active components by applying Michie's Behaviour Change Technique Taxonomy (Michie et al, 2013).…”
Section: Methodsmentioning
confidence: 99%